Everyday Problems With Executive Dysfunction and Impulsivity in Adults Recovering From Methamphetamine Addiction. (March 2016) - Ellis, Carilyn; Hoffman, William; Jaehnert, Sarah; Plagge, Jane; Loftis, Jennifer M.; Schwartz, Daniel; Huckans, Marilyn
Abstract : Objectives: Compared with nonaddicted controls (CTLs), adults in remission from methamphetamine addiction (MA-REM) evidence impairments on objective measures of executive functioning and impulsivity. Methods: To evaluate the impact of these impairments in MA-REM adults, demographically matched groups (MA-REM, n=30; CTLs, n=24) completed objective and self-report measures of executive functioning and impulsivity. Results: MA-REM adults demonstrated significantly ( P <0.050) greater objective and subjective problems with executive functioning and impulsivity. Conclusions: These results suggest that adults in MA-REM are aware of their deficits and that these deficits have significant impact in everyday life.